Poor compliance with clinical practice guidelines in the management of asthma in primary care in the community of Madrid - María Leyre Román Villaizán; Andrea Seoane Sanz; Teresa Sanz Cuesta; Ricardo Rodríguez Barrientos; Tamara Alonso Safont; Carmen Villaizán Pérez; Manuel Praena Crespo (Elsevier, 2024)
Introduction: Asthma is a common chronic disease in the paediatric age group that requires close follow-up. Clinical practice guidelines offer evidence-based recommendations to achieve adequate control of the disease. Objective: To assess the management of childhood asthma in the primary care setting in the Community of Madrid, and the adherence of health care professionals to guideline recommendations. To analyse the association of asthma management with age, the socioeconomic level of the catchment population and the workload of primary care centres. Methods: retrospective longitudinal study in patients aged 6-14 years newly diagnosed with asthma in primary care centres of the Community of Madrid in 2021. We analysed sociodemographic and clinical variables and the compliance with recommendations at the time of diagnosis and over 1 year of follow-up. The source of data was the electronic health record database of the primary care system. Results: We found a proportion of compliance with the recommendations upon diagnosis of the disease of 5.84%, with differences associated to the socioeconomic level of the catchment population (P = .033), and the pressure of care (P = .006). The proportion of compliance with recommendations during follow-up was 12.73%, with differences based on age (P = .01), socioeconomic level (P = 0.006) and centre workloads (P = .002). Conclusions: Compliance with the recommendations of the main childhood asthma management guidelines in the primary care setting was low in the Community of Madrid. Strategies need to be implemented to improve the management of this disease and the adherence of professionals to the protocols developed for this purpose. Resumen: Introducción: El asma es una enfermedad crónica frecuente en la edad pediátrica y precisa un seguimiento estrecho. Para lograr un buen control de la enfermedad las Guías de Práctica Clínica ofrecen recomendaciones basadas en la evidencia científica. Objetivo: Valorar el manejo del asma que se realiza en Atención Primaria de la Comunidad de Madrid, y la adecuación a las recomendaciones de las guías por parte de los profesionales sanitarios. Analizar la relación del manejo con la edad, el nivel socioeconómico de la población y la presión asistencial de los centros de salud. Métodos: Estudio longitudinal retrospectivo en pacientes de 6 a 14 años con un nuevo diagnóstico de asma durante el año 2021 en los centros de salud de la Comunidad de Madrid. Se analizaron variables sociodemográficas, clínicas y el cumplimiento de las recomendaciones al diagnóstico y durante un año de seguimiento. La fuente de información fue la Historia Clínica Electrónica para Atención Primaria. Resultados: El cumplimiento de las recomendaciones al diagnóstico de la enfermedad fue del 5,84%, con diferencias según el nivel socioeconómico (p = 0,033) y la presión asistencial (p = 0,006). El cumplimiento de las recomendaciones durante el seguimiento fue del 12,73%, con diferencias según la edad (p = 0,01), nivel socioeconómico (p = 0,006) y la presión asistencial (p = 0,002). Conclusiones: El cumplimiento registrado de las recomendaciones sobre el manejo del asma en Atención Primaria de la Comunidad de Madrid es bajo. Es necesario fomentar estrategias para mejorar el manejo de esta enfermedad y, la adhesión de los profesionales a los programas diseñados para ello.